INOVASI PRODUK DAN LAYANAN BUMDES UNTUK MENINGKATKAN PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT DESA BUNGA EJA - Nispa Sari; Altri Wahida; Rifqa Ayu Dasila (Universitas Mataram, 2026)
This Community Service aims to enhance the capacity and skills of the Village-Owned Enterprises (BUMDes) managers in developing a sustainable and competitive village business. Through outreach and training on product and service innovation, BUMDes managers gain an understanding of the importance of creativity and innovation in creating products and services that meet local and market needs. BUMDes management training focuses on improving business management effectiveness, covering strategic planning, organizing, and operational control. Additionally, entrepreneurship seminars aim to inspire entrepreneurship among participants, emphasizing risk-taking and adaptation to changes in the business environment. Financial management application training introduces technology for more efficient and accountable financial recording and reporting. The results of this program indicate an improvement in BUMDes managers’ abilities in innovation, management, entrepreneurship, and technology use. This initiative is expected to support the development of a more professional, transparent, and sustainable BUMDes, thereby enhancing the welfare of the village community.